Understanding the Emergence of Multidrug-Resistant Candida: Using Whole-Genome Sequencing to Describe the Population Structure of Candida haemulonii Species Complex - Gade, Lalitha; Muñoz, Jose F.; Sheth, Mili; Wagner, Darlene; Berkow, Elizabeth L.; Forsberg, Kaitlin; Jackson, Brendan R.; Ramos-Castro, Ruben; Escandón, Patricia; Dolande, Maribel; Ben-Ami, Ronen; Espinosa-Bode, Andrés; et al. (Frontiers in Genetics, 2020)
The recent emergence of a multidrug-resistant yeast, Candida auris, has drawn attention to the closely related species from the C. haemulonii complex that include C. haemulonii, C. duobushaemulonii, C. pseudohaemulonii and recently identified C. vulturna. Here, we used antifungal susceptibility testing and whole genome sequencing (WGS) to investigate drug resistance and genetic diversity among isolates of C. haemulonii complex from different geographic areas in order to assess population structure and the extent of clonality among strains. Although most isolates of all four species were genetically distinct, we detected evidence of the in-hospital transmission of C. haemulonii and C. duobushaemulonii in one hospital in Panama indicating that these species are also capable of causing outbreaks in healthcare settings. We also detected evidence of the rising azole resistance among isolates of C. haemulonii and C. duobushaemulonii in Venezuela, Colombia and Panama linked to substitutions in ERG11 gene, as well as amplification of this gene in C. haemulonii in isolates in Colombia suggesting the presence of evolutionary pressure for developing azole resistance in this region. Our results demonstrate that these species need to be monitored as possible causes of outbreaks of invasive infection.